Interest and motivation of disadvantaged students toward online learning during the COVID-19 pandemic in Nepal - Nepal, Ratna Mani; Khadka, Bimal; Guragain, Shyam; Ghimire, Jiwnath (Frontiers in Education, 2024)
Online learning and teaching during the Covid-19 pandemic had mixed impacts on students' accessibility and performance. It benefited the concerned stakeholders, including management, teachers, and the students, to retain in the system, but it reinforced pre-existing discrimination among students from various disadvantaged groups. Studies reveal that the online learning system created an environment that facilitated students' motive and interest in learning who disengaged themselves from classrooms due to various socio-economic reasons during the pandemic. The present study explored students' experience and perception of online learning in Nepal and analyzed the predictors of their interest in participating in the new learning environments. More specifically, it studied how the online modes of learning were associated with the interests of disadvantaged higher education students in their academic pursuits during the Covid-19 pandemic and how online learning impacted the pre-existing discriminations among them. The study generated concepts and variables drawing from the technology acceptance model (TAM) and a review of existing literature. A survey among 324 higher education students and a follow up interview among nine selected respondents were conducted in Nepal between April to June 2021. The sample represented students from all social classes, genders, financial status, and geographies. Using a logistic regression model of the survey data and thematic analysis of interviews, this study found that compared to others, students from disadvantaged groups were significantly motivated by the online learning system. Their perception of online learning was positive despite the shortcomings of the system, such as the lack of internet infrastructure and the continuous flow of electricity. Students' motivation towards the online learning system was triggered by their perception, which helped them to retain and continue in the higher education system. Based on the findings, this study concludes that in a developing country like Nepal, where students face social, economic, and geographical challenges in accessing higher education, the online learning system could be an effective alternative to traditional face-to-face learning to minimize preexisting discrimination.